Climate Smart Crop-Small Ruminant Value Chain: a Rapid Assessment of Gender Gaps and Opportunities In Doyogena, SNNPR, Ethiopia - Tadesse, Meron; Ambaw, Gebermedihin; Mungai, Catherine; Kuma, Simegn; Radeny, Maren A.O.; Tamene, Lulseged D.; Auma, Joseph; Solomon, Dawit (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2022)
The majority of smallholder farmers in Ethiopia depend on rainfall-fed subsistence agriculture for their livelihoods and are highly vulnerable to climate change and variability. To address the negative impacts of climate change, climate-smart agriculture technologies are implemented and practiced in Doyogena climate-smart landscape. However, there are specific CSA activities that need gender mainstreaming. These include solar-irrigated agricultural systems, integrated rural aquaculture with crop and livestock systems, improved agronomic practices, value-added CSA products, financial and non-financial support services, and linking farmers to markets through joint actions. For this purpose, a needs assessment was conducted using rapid gender gaps assessment (RGA). Through FDGs, KIIs, and household surveys, the RGA identified gender gaps such as differences in access to and control over productive assets/resources, limited decision-making power by women, lack of specific leadership development program by the government to promote women's participation in decision-making processes, restricted mobility, lack of access to capacity building, formal financial services including credit, and production and market information, lack of targeted policy which adequately support and offer legal protection to women, male-labor shortage and systematic discrimination from extension provision services, challenges of food security, ownership of fewer and smaller farm plots, and lack of coordinated plans and platforms for intervention by stakeholders and gender advocates in the district. As a result, there are fewer options for women to engage in opportunities available to members of the community within and beyond their localities, restricted marketing opportunities and limited income earning options, and limited control and use of the available assets/resources, which in turn constrain their access to credit as they lack collateral. The RGA revealed gender inequality at household, community, and government institutions levels.